Dynamics of Academic Emotions of Pre-service Teacher Professional Education Students - Akhmad Harum; Muhammad Anas; Suciani Latif (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Academic emotion is a psychological condition experienced by students before, during, and after carrying out academically demanding activities. The academic emotions experienced by PPG students are divided into positive and negative. This study aims to determine the academic emotions of Pre-service PPG students in terms of gender, origin from PT, and regional origin and find out the dynamics of academic emotions seen from the causes and effects of the emotions that occur. This research uses descriptive quantitative using the Achievement Emotions Questionnaire (AEQ) instrument developed by Pekrun, which is modified into 62-item statements that measure groups of academic emotions (positive-activation, negative-activation, and negative-deactivation) and observation. The instrument was validated using confirmatory factor analysis and reliability tests on JASP. The research sample was Pre-service PPG Students in the Guidance and Counseling study field, totaling 36 people. Data analysis used descriptive analysis and ANOVA. The study results show that students' academic emotions are high. PPG students have types of positive emotions and negative emotions. In the gender aspect, female students show negative emotions more quickly than men and positive ones. However, in the aspect of regional origin and PT, there is no significant difference. The positive and negative emotions experienced by students are caused by many internal and external factors that affect academic success in undergoing Pre-service PPG